2008
DOI: 10.1097/ypg.0b013e3282df0939
|View full text |Cite
|
Sign up to set email alerts
|

Effect of genetic polymorphisms on smoking cessation: a trial of bupropion in Korean male smokers

Abstract: It can be concluded that genetic diversity might determine the effects of bupropion on smoking cessation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 26 publications
3
45
0
Order By: Relevance
“…One study found no association between COMT genotype and smoking intensity (David et al 2002, McKinney et al 2000, whereas another found the GG genotype to be associated with smoking at least one pack per day (Tochigi et al 2007). In studies that examined COMT in relation to smoking abstinence in randomized treatment trials of smoking cessation, observations have varied from no association (Ton et al 2007), to the AG/GG genotypes being associated with quicker relapse (Munafo et al 2008), to the GG genotype being associated with smoking abstinence (Han et al 2008). In another study, the G allele was observed to be protective against nicotine dependence (Beuten et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study found no association between COMT genotype and smoking intensity (David et al 2002, McKinney et al 2000, whereas another found the GG genotype to be associated with smoking at least one pack per day (Tochigi et al 2007). In studies that examined COMT in relation to smoking abstinence in randomized treatment trials of smoking cessation, observations have varied from no association (Ton et al 2007), to the AG/GG genotypes being associated with quicker relapse (Munafo et al 2008), to the GG genotype being associated with smoking abstinence (Han et al 2008). In another study, the G allele was observed to be protective against nicotine dependence (Beuten et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Higher DBH plasma concentrations may influence drug dependence (Cubells et al 2000, Gabel et al 1995. However, so far the evidence concerning variants in the COMT, DBH and MAO-A genes in relation to smoking behaviors has been inconsistent (Beuten et al 2006, Colilla et al 2005, David et al 2002, Enoch et al 2006, Guo et al 2007, Han et al 2008, Jin et al 2005, Johnstone et al 2004, McKinney et al 2000, Munafo et al 2008, Tochigi et al 2007, Ton et al 2007). …”
Section: Catechol-o-methlyltransferase (Comt) Dopamine Beta-hydroxylmentioning
confidence: 99%
“…However, Swan et al [2005] observed these effects only in women. Nevertheless, Han et al [2008] reported that smokers having both homozygote genotypes (A1/A1 or A2/A2) had higher abstinence rates than heterozygotes (A1/A2).…”
Section: Bupropionmentioning
confidence: 94%
“…The single study analyzing association between DRD4 exon III 48-bp VNTR genotypes and smoking cessation following bupropion therapy found no significant results [Han et al, 2008]. There was also no association between 5-HTTLPR genotypes and response to bupropion treatment [Han et al, 2008].…”
Section: Bupropionmentioning
confidence: 96%
See 1 more Smart Citation